3-Dimensional CBCT analysis of mandibular asymmetry in unilateral condylar hyperplasia. Issue 12 (December 2016) - Nolte, Jitske Willemijn; Verhoeven, Tim Jan; Schreurs, Ruud; Bergé, Stefaan Jozef; Karssemakers, Luc Hendrikus Elisabeth; Becking, Alfred Gustaaf; Maal, Thomas Jan Jaap
Abstract: Purpose: Three-dimensional quantification of asymmetry in UCH has not been reported yet, but would be useful for diagnosing and evaluating the degree of deformity in this disease. It enables profound decision-making and timing of surgery. Unilateral condylar hyperplasia (UCH) can subjectively be classified in hemimandibular elongation (HE), hemimandibular hyperplasia (HH) and a combination of these two (hybrid form). The main purpose of this study was to quantify mandibular asymmetry in UCH patients with a reliable and reproducible method. Secondly, it was evaluated whether the existing classification can be confirmed. Materials and methods: 37 UCH-patients with progressive mandibular asymmetry, supported by a positive bone scan and/or such clinical progression that condylectomy was performed, were included in this retrospective study. A group of healthy subjects, matched for age and gender, was used as the control group. Cone-beam computed tomography (CBCT) scans were imported in Maxilim ® software. Each mandibular half was divided into three skeletal segments (condyle, ramus, and body). Linear and volumetric measurements were calculated for these skeletal units on the affected and unaffected side, for both patients and controls. Results: Significant differences between affected and unaffected sides in the patient group were found in condylar, ramus, and body segments for linear (p < 0.01) as well as for volumetric quantitative measurements (p < 0.0040). A mean linear difference between affected and unaffected sides in the condylar region of the UCH patient group was found of 3.6 mm (sd 2.9) versus 0.2 mm (sd 1.5) in controls. For volumetric measurements there was a mean difference between the left and right condyle of 718 mm 3 (sd 638) in the patient group versus 8 mm 3 (sd 225) difference in the control group. The condyle was the most affected segment. Differences between sides were significantly larger in the patient group than in the control group (p < 0.001). It was not possible to objectify differences between HE and HH. Conclusion: CBCT is a useful and accurate modality for quantification and evaluation of mandibular asymmetry in UCH. It enables objective monitoring. The existing classification in HE and HH could not be confirmed.